PHYTOCHROME INTERACTING FACTORS mediate metabolic control of the circadian system in Arabidopsis. Issue 1 (25th April 2017) - Shor, Ekaterina; Paik, Inyup; Kangisser, Shlomit; Green, Rachel; Huq, Enamul
Summary: The circadian ( c . 24 h) system has a central role in regulating the timing and coordination of photosynthesis, and in turn photosynthesis and photosynthetic products which are controlled by the circadian clock feedback to affect the circadian oscillator that generates rhythms. However, little is known about the mechanism(s) by which this feedback occurs. One group of likely candidates for signal transduction to the circadian clock are the PHYTOCHROME INTERACTING FACTOR (PIF) family of transcription factors which have been shown to be involved in numerous signaling pathways in Arabidopsis. Yet despite evidence that some PIF genes are under circadian control and bind promoter motifs present in circadian genes, until now PIFs have not been shown to affect the circadian system. Using a range of techniques, we have examined how circadian rhythms are affected in higher order pif mutants and the mechanisms by which PIFs regulate signaling to the circadian clock. We show that PIFs mediate metabolic signals to the circadian oscillator and that sucrose directly affects PIF binding to the promoters of key circadian oscillator genes in vivo that may entrain the oscillator. Our results provide a basis for understanding the mechanism for metabolic signaling to the circadian system in Arabidopsis.